MACROECONOMIC FACTORS OF NON-PERFORMING LOANS IN COMMERCIAL BANKS - Mileris, Ričardas (Ekonomika, 2014)
Abstract. This article presents an analysis of macroeconomic factors and their impact on the percentage of non-performing loans (NPLs) in commercial banks of the EU countries. This problem is relevant because in recent years many EU countries had the economic downturns that can be visible in the main macroeconomic indicators. Also, banks have met the growth of non-performing loans when the debtors were not able to meet their financial obligations. The Basel III Agreement notes the necessity to consider the economic conditions of a country when assessing the credit risk of loan applicants. The results of this research can be useful for banks, because the main relations between macroeconomics and non-performing loans have been revealed. Since 2009, Lithuania has one of the highest NPL percentage in the EU, and the meaningful impact of economic deterioration on the debtors‘ ability to repay debts to banks has been proven. The same situation was ascertained in other EU countries with imperfect economic conditions. Conversely, it has been estimated that banking systems in the EU countries with developed economies are not very sensitive to the business cycle fluctuations. So, in Lithuanian banks, when managing credit risk, the consideration of economic conditions is very important.Key words: banks, credit risk, macroeconomics, non-performing loans